Influencing factors for pediatric eye disorders and health related quality of life: a cross-sectional study in Shanghai, China - Shu, Qin; Xiao, Zhongzhou; Peng, Xinwei; Liang, Xiaoyi; Chen, Moxin; Tao, Zhuoran; Liu, Qianwen; Guo, Yonglin; Yang, Xuefeng; Nie, Wanqin; Chen, Ruiyao; Yang, Liya; et al. (Frontiers in Medicine, 2024)
Background: Myopia, strabismus and ptosis are common pediatric eye diseases, which have a negative impact on children and adolescents in terms of visual function, mental health and health-related quality of life (HRQoL). Therefore, this study focused on those pediatric eye diseases by analyzing their risk factors and HRQoL for the comprehensive management of myopia, strabismus and ptosis. Methods: A total of 363 participants (2-18 years old) were included in this study for risk factors analysis of myopia, strabismus and ptosis. We collected demographic characteristics, lifestyle habits and eye care habits of these children and analyzed them by using univariable and multivariable logistic regression. In addition, we applied the Chinese version of Pediatric Quality of Life Inventory-Version 4.0 (PedsQL 4.0) to assess HRQoL in 256 children with strabismus and ptosis. Univariable and multivariable linear regression models were applied to evaluate potential influencing factors of HRQoL.Results: Of all the participants, 140 had myopia, 127 had strabismus, and 145 had ptosis. Based on the multivariable logistic regression analysis model, we found that the history of parental myopia and daily average near-distance eye usage time were risk factors for myopia, and increased body mass index (BMI) was identified as a risk factor for strabismus and ptosis. Individuals with ptosis possessed decreased HRQoL. The multivariable linear regression model suggested that daily average near-distance eye usage time, light intensity during visual tasks, and daily average sleep duration had potential influences on HRQoL. Conclusion: This is the first study to assess the risk factors and HRQoL of myopia, strabismus, and ptosis together. We identified risk factors for these common pediatric eye diseases to help doctors, parents, and teachers better manage them. Our study discovered that children with eye disorders exhibit a notably diminished HRQoL. Consequently, it emphasizes the necessity for increased social attention and mental health assistance for these children.